Will increasing access to mental health treatment close India's mental health gap? - Lesley Jo Weaver; Alison Karasz; Kiranmayee Muralidhar; Poornima Jaykrishna; Karl Krupp; Purnima Madhivanan (Elsevier, 2023)
Background: India's National Mental Health Survey (NMHS) reports a treatment gap for common mental disorders of over 85 percent, which they attribute to lack of awareness and access to psychiatric services in India. Interventions aiming to close that treatment gap through task-sharing have gained significant traction in India, but have met with mixed success, particularly in long-term perspective. Aims: We critically examined the assumptions embedded in the NMHS report that the mental health treatment gap results from people in India lacking access and awareness to psychiatric services in a medium-sized Indian city. Method: We conducted qualitative interviews with a community-based sample of 66 adult women in Mysuru city, Karnataka about the causes of distress in their lives, their understandings of distress, and their care-seeking behaviors. The overall aim was to assess their familiarity with psychiatry and their relative willingness to engage with it. Results: Women were familiar with psychiatric models of mental illness and with the psychiatric services available in their community. They recommended these services for hypothetical others but uniformly refused them for their own distress, even when this distress was severe. Women reported fears of stigma, doubts about psychiatric effectiveness, and connected their distress to social and structural causes rather than medical causes. They therefore did not perceive that clinical care could help them resolve their distress. Conclusions: Cultural mismatch appeared to be responsible for at least a part of women's lack of use of psychiatry in the research context. We conclude with a set of recommendations addressing how future research and intervention could modify task-sharing approaches to incorporate culturally relevant conceptions of distress and its appropriate management, instead of relying solely on standard psychiatric approaches.